Comparative Study of In Vitro Root and Shoot Proliferation from the Node Explants of Asparagus racemosus Willd - Pant, K. K.; Joshi, S. D. (Journal of the Institute of Agriculture and Animal Science, 2018)
Asparagus racemosus Willd. locally known as Kurilo or Shatavari is found throughout the tropical and subtropical regions of Nepal. It is a high value herb because of its medicinal and nutritional values which is leading this species decrease in its natural habitat. Hence, to conserve this species, an in vitro tissue culture method of its multiplication has been applied as an effective method of ex situ conservation. In the experiment, although most of the treatments induced highly insignificant number of adventitious shoots, low concentration of IBA (0.1-0.5 mg/l) in combination with relatively higher concentrations of Kinetin (1.0-2.0 mg/l) in MS medium were found to be significantly inducing up to 8.33±1.308 shoots/node. Among the treatments where hormones were used singly, IAA 0.5 and Kinetin 1.0 induced 4.83±1.08 and 4.66±1.43 shots/node respectively. Hence, a protocol for the effective multiplication of this species has been developed which can be used accordingly.